Resolution of Banking Crises : The Good, the Bad, and the Ugly - Laeven, Luc (IMF Working Papers; Working Paper ;, 2010)
This paper presents a new database of systemic banking crises for the period 1970-2009. While there are many commonalities between recent and past crises, both in terms of underlying causes and policy responses, there are some important differences in terms of the scale and scope of interventions. Direct fiscal costs to support the financial sector were smaller this time as a consequence of swift policy action and significant indirect support from expansionary monetary and fiscal policy, the widespread use of guarantees on liabilities, and direct purchases of assets. While these policies have reduced the real impact of the current crisis, they have increased the burden of public debt and the size of government contingent liabilities, raising concerns about fiscal sustainability in some countries.